The Survival Strategy of Halal Tourism in Covid-19 Pandemic Era - Muawanah Muawanah; Nur Dinah Fauziah; Mohamad Toha; Agnes Cahyatria Manaku (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2021)
Halal tourism has great potential for the Indonesian economy and is currently trying to defend its sector from the Covid-19 or corona virus outbreak. Covid-19 is one of the outbreaks that has been declared a pandemic because it is a global disease spreading very quickly. Covid-19 is a new virus originated in Wuhan, China in 2019 and has spread to almost all countries in the world, including Indonesia. The impact of this virus is felt by everyone in the world. It even threatens all sectors that affect the economy. Among these sectors is halal tourism. Therefore, the halal tourism sector is currently preparing a strategy to stay afloat even in situations and conditions like this as a preparation for the post-Covid-19. The strategy of the Indonesian state in maintaining halal tourism is to prioritize improving destinations, preparing budget support from cooperation with halal tourism, providing mitigation SOPs, strengthening regulations for tourists from abroad entering Indonesia.